ANALISIS FINANSIAL AYAM RAS PEDAGING (Kasus Pembesaran Ayam Ras Pedaging di Kecamatana Bekasi Barat) - Nursinah, Is Zunaini; Lutfiadi, Ridwan; Mustaiem, Mustaiem (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Livestock industry aims to expand jobs and trying to increase the consumption of animal protein communities through the provision of meat, eggs, and dairy development. One of the cattle business has a good prospect of broiler business is that demand continues to increase along with the increase of population. The purpose of research is to look at business development and the sensitivity of broiler business. The research method used was the case study method. The data used in the analysis is the analysis of feasibility are: Net Present Value (NPV), Internal Rate of Return (IRR) and Sensitivity Analysis. The results showed that the chicken business "Tani Rahayu" deserves to be developed with a NPV of Rp 654.093.820,00, 30.1% IRR, B-C ratio 2,1, and a PP of 1,9 years.